Uji Efek Antipiretik Ekstrak Etanol, Fraksi N-Heksana dan Fraksi Etil Asetat Daun Beringin (Ficus Benjamina L.) pada Tikus Putih Jantan (Rattus Norvegicus) - Hasti, Syilfia; Sandi, Nofri Hendri; Srianti, Teti (Jurnal Sains dan Teknologi Farmasi, 2012)
Banyan plant has been used by communities as a traditional medicine in order to heal heat cramps in children but it has not been scientifically tested. A study has been conducted to observe an antipyretic effect of the ethanolic extract, the fraction of n-hexane and ethyl acetate fraction of the leaves of banyan (Ficus benjamina. L) in male white rats (Rattus norvegicus) with fever induction method using a solution of peptone 2% as much as 0.5 mL / 200 g body weigt intra peritonially, with the dose of ethanol extract, the fraction of n-hexane and ethyl acetate fractions 100, 200, and 400 mg / kg orally. Respectively as a positive control, asetosal was administered at a dose 117 mg / kg and the negative control was 1% CMC Na. Temperature observations of mice performed at 30, 60, 90, 120, 150, and 180 minutes, then percent protection was calculated. Data analysis was done using Two-way Analysis of Variance (ANOVA) and Tukey test. Results showed that the fraction of n-hexane at a dose of 400 mg/kg had an antipyretic effect as significantly (p<0.05).